The Efficacy of Platelet-Rich Plasma Injection Therapy in Obese versus Non-Obese Patients with Knee Osteoarthritis: A Comparative Study - Annaniemi, Juho A. (MPDI, 2025)
Background/Objectives: Obesity is a common comorbidity in knee osteoarthritis (KOA) patients. Platelet-Rich Plasma (PRP) injection therapy may mitigate KOA. To further clarify potential patient selection for PRP injection therapy, we compared the outcomes in patients with different body mass index (BMI).
Methods: A total of 91 patients with mild to moderate KOA were treated with three intra-articular PRP injections at 10 to 14-day intervals. Range of motion (ROM), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and Visual Analogue Scale (VAS) were documented before and after the injections at 15 days, 6 months, 12 months, and at the last follow-up. Outcomes were compared between patients with a BMI over 30 kg/m2 (obese, n = 34) and under 30 kg/m2 (non-obese, n = 57).
Results: Significant difference during the follow-up was detected in WOMAC score at the last follow-up favouring BMI under 30 group [17.8 ± 18.8 versus 10.5 ± 11.7, p = 0.023]. The odds ratio (OR) in BMI over 30 kg/m2 group for total knee arthroplasty was 3.5 (95% CI 0.3-40.1, p = 0.553), and OR for any arthroplasty was 7.5 (95% CI 0.8-69.8, p = 0.085) compared to non-obese patients.
Conclusions: Obese patients benefitted from PRP injections in KOA but there is a minimal difference favouring non-obese patients in symptom alleviation in follow-up stages after 12 months. The risk of arthroplasty is higher for obese KOA patients.